Effect of Tungsten Addition on Continuous Cooling Transformation and Precipitation Behavior of a High Titanium Microalloyed Steel - Zhenqiang Wang; Dongshen Huo; Yanyuan Zhou; Guoying Sui; Fengchun Jiang (Metals, 2022)
Effects of tungsten addition on the continuous cooling transformation (CCT) characteristics and precipitation behavior of a high titanium microalloyed steel were investigated by dilatometry, optical microscopy, scanning and transmission electron microscopy, and hardness measurements. The results showed that the ranges of transformation products were moved to the right side of the CCT diagram when the 0.4% W was added. Accordingly, the following observations were made: (i) the ferrite phase transformation was shifted to the side of lower cooling rates and reduced temperatures; (ii) the bainite phase transformation region ran throughout the whole cooling rate range studied. Addition of W had a positive effect on the particle size refinement and number density increase of the precipitates. At the low cooling rates, in the range of <14 °C/s, W addition shifted the precipitation hardening peak to the low cooling rate side as the ferrite transformation induced stronger precipitation strengthening than the bainite one. Furthermore, the effect of W addition on phase transformation strengthening was obvious (increase in hardness: ~40Hv) at the high cooling rate range, over 14 °C/s.